Growth patterns of Holstein Friesian Dairy Cow (FH) from Birth to First Child based on Mathematical Analysis of the Gompertz Model - Desi Ratnasari; Afton Atabany; Bagus Priyo Purwanto; Lia Budimulyati Salman (Faculty of Animal Science, Universitas Gadjah Mada, 2019)
This aims of this study was to estimate the bodyweight of FH dairy cows from birth to first child by knowing growth patterns and creating a standard curve for dairy cattle growth at BBPTU-HPT Baturraden dairy cow in Baturraden district, Banyumas Regency, Purwokerto, Central Java. Data obtained in the form of secondary data from births in 2005-2016 were 1437 tails and primary data were 353 tails. Data were analyzed using SAS 9.4 program with NLIN procedures (Non-Linear) using Gompertz models. The results show that the Gompertz models is easy in the calculation process with the data deviations that are close to the field of data and the models have a high degree of accuracy with the coefficient of determination (R2 ) 99.83%. The conclusion of this study is that the resulting curve of the Gompertz model can be used as a standard growth curve of Friesian Holstein dairy cattle in Indonesia from birth to first calf.